A Note on the Numerical Solution of Coupled Klein-Gordon Equations - Yildirim, Ozgur; Uzun, Meltem (AMER INST PHYSICS, 2019)
This study presents the numerical solution of coupled Klein-Gordon equations, which models exchange of energy between two different components of one-dimensional nonlinear wave process. A composite numerical method based on the first order of accuracy finite different scheme and fixed point iteration is implemented to solve coupled Klein-Gordon equations with appropriate initial and boundary conditions. A test problem is employed and results of numerical experiments are presented with error analysis.
Keywords: Existence; Uniqueness; Weak solutions; Finite Difference; Fixed Point Theory; Mathematics; Physics